Oxidative metabolism and antioxidant capacity associated to UV radiation effects in photosynthetic organisms - Galatro, Andrea Verónica (2011)
The stratospheric ozone layer which attenuates solar ultraviolet-B (UV-B) irradiation (290-320 nm) is being depleted by pollutants such as chlorofluorocarbons. It has been postulated that if as a result of ozone loss, UV-B flux at the surface of the earth increases, negative impacts on biological organisms will be inevitable since UV-B radiation causes a multitude of physiological and biochemical changes in photosynthetic organisms. Among other parameters, photosynthesis is impaired, pigment composition is altered, and the expression of the genes which encode for antioxidants are induced. Ultraviolet light has been shown to be very effective in inducing lipid peroxidation of biological membranes, polyunsaturated fatty acids and phospholipid liposomes. It has been also reported that UV-B can destroy the natural liposoluble antioxidants and promote the formation of lipid peroxidation products. The photosynthetic pigments are affected and consequently the production of energy and reduction equivalents decrease, which in turn hampers CO2 incorporation into organic material. The pigments of the photosyntheticapparatus are affected by solar or artificial UV radiation. The carotenoids, which operate as protective pigments against excessive irradiation, are bleached and eventually the chlorophyll, vital for photosynthetic energy transformation, is destroyed. In this complex scenario, the mechanisms of biological effects of near UV appear to involve endogenous photosensitization and formation of reactive oxygen species (ROS). The aim of this work is to briefly summarize and update the data on the stress response of photosynthetic cells (both, algae and plants) after exposure to UV-B radiation, comparatively analyzing the effects on the rate of growth, chlorophyll content and chloroplast function described by our laboratory. The profile of the content of lipid-soluble and water-soluble antioxidants is described and analyzed in a general frame to search for adaptive responses.